2019
DOI: 10.1002/ecs2.2803
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging differences: number, characteristics, and distribution of marine benthic communities along Taiwan coast

Abstract: Our knowledge of the ability of coral reefs to face contemporary challenges disregards the wide variety of benthic communities (BCs) that could be associated with contrasted dynamics when facing stressors. Accordingly, this study investigates the number, characteristics, and distribution of BCs responsible for the development of coastal three‐dimensional structures in Taiwan. A total of 89 transects among three regions (north, east, and south) and two depths (−10 and −40 m) were characterized using a morpho‐fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 92 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…This means the relationships between different taxa and light across depth gradients need to be quantified (Edmunds, Tsounis, Boulon, & Bramanti, 2018; Kleypas, Mcmanus, & Meñez, 1999; Lesser et al., 2018; Muir et al., 2018). Recent studies in the Red Sea have shown this can be achieved at a community level by linking light data (Tamir et al., 2019) to cluster analyses of co‐occurring coral taxa (Laverick et al., 2017; Lin & Denis, 2019). Similarly, in upper mesophotic sites throughout the central Indo‐Pacific, light controls community structure in tandem with hydrodynamic effects (Turak & DeVantier, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This means the relationships between different taxa and light across depth gradients need to be quantified (Edmunds, Tsounis, Boulon, & Bramanti, 2018; Kleypas, Mcmanus, & Meñez, 1999; Lesser et al., 2018; Muir et al., 2018). Recent studies in the Red Sea have shown this can be achieved at a community level by linking light data (Tamir et al., 2019) to cluster analyses of co‐occurring coral taxa (Laverick et al., 2017; Lin & Denis, 2019). Similarly, in upper mesophotic sites throughout the central Indo‐Pacific, light controls community structure in tandem with hydrodynamic effects (Turak & DeVantier, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade (2009–2018), economic development has increased the number of tourists in the region from 3.5 million to over 8 million, with human activities peaking in summer ( Maynard et al, 2019 ). Land-based pollution ( Meng et al, 2008 ; Liu et al, 2012 ; Jiang et al, 2015 ) and overfishing ( Liu et al, 2009 ) were previously hypothesized to conjointly impact both the heterogeneity observed in the structure of the benthic communities ( Ribas-Deulofeu et al, 2016 ) and the benthic diversity of KNP ( Lin & Denis, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The algae were divided into 11 OTUs: three macrophyte OTUs (green, red, and brown), six filamentous OTUs (brown, green, red, Cyanophyta, turf, and turf sedimented) and two calcareous OTUs (Encrusting Coralline Algae [ECA] and articulated calcareous algae) ( Titlyanov & Titlyanov, 2012 ). Octocorals (10 OTUs) were identified at the genus level ( Fabricius & Alderslade, 2001 ) and associated with a morphotype (clustered, columnar, bushy, digitate, lobate, or massive) following Lin & Denis (2019) . Data was later summarized into 14 major categories (Ascidian, Encrusting Coralline Algae, Hydrozoan, Macro-algae, Octocoral, Scleractinian, Sea Anemone, Sponge, Turf, Zoantharian, Other Life, Unknown, Bare, and Unstable Substrate).…”
Section: Methodsmentioning
confidence: 99%
“…Shallow reefs at Guiwan and Dabaisha consist of fringing reef structures which are subjected to high‐energy hydrodynamic transport (Lau et al., 2015). These benthic communities are characterized by arborescent, bushy, and tabular hard corals, clustered octocorals, and encrusting actinarians (Lin & Denis, 2019). MCEs at Guiwan and Dabaisha exhibit limited hard substrates interspersed with sediment and rubble (Denis et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This study details a census and comparison of coral recruitment in shallow and mesophotic reef communities at Ludao, an island off southwestern Taiwan. Shallow and mesophotic communities at Ludao have been shown to possess distinctive communities, despite similarities in coral assemblages (Lin & Denis, 2019). In the past, assessments of recruitment in Taiwan were conducted above 15m (Edmunds et al., 2014; Ho & Dai, 2014; Nozawa et al., 2013; Soong et al., 2003) and all have identified recruits morphologically, except Hsu et al.…”
Section: Introductionmentioning
confidence: 99%